Analisis Kritis M. Quraish Shihab Terhadap Karakteristik Kepemimpinan Dalam Tafsir Al-Mishbah - Romziana, Luthviyah; Fajarwati, Linda (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2023)
As we know today there are many differences of opinion and controversy from the political elite of statesmen even Ulama in Indonesia about the feasibility of personnel character that must be owned by a leader. Al-Quran has talked a lot about the characteristics of leaders from various aspects. This matter shows that the urgency of character for a leader cannot be separated from Al-Quran values. This article is present to know the verses of the Al-Quran which discusses the characteristics of leaders and their specifications with the method interpretation that focuses on one character with his book of interpretation, namely Tafsir al-Misbah written by M. Quraish Shihab. This written belongs to research literature with a content analysis approach. With the source of primary data from the book of Tafsir and the Al-Quran. The techniques of data collection are carried out through studies literature by tracing the books of commentary that contain the theme, with using the library research method which is then described in written form (descriptive text) While the data analysis technique is carried out by content analysis method. After doing the research, the writer found the verses that related to the characteristics of leadership in the Al-Quran, which is found in the surah Ali Imran 159, At-Taubah 105, Al-Ahzab 70, At-Taubah 71. Relying on the 4 surah In this paragraph, specifically, this verse explains that to achieve a good leader, good should start with goodness that comes from the leader himself. Such as being gentle, fair, honest, telling the righteous, prevent the wrong, forgive when angry, and involve deliberation in every problem. In this way, a leader can lead and bring the world for the better